Mechanical, biocompatibility and antibacterial studies of gelatin/polyvinyl alcohol/silkfibre polymeric scaffold for bone tissue engineering - Sabareeswari Kalidas; Shanmugam Sumathi (Heliyon, 2023)
The current study focuses on the incorporation of natural polymers (gelatin, silk fibre) and synthetic (polyvinyl alcohol) polymer towards the fabrication of a novel composite for bone tissue engineering. The Electrospinning method was used to fabricate the novel gelatin/polyvinyl alcohol/silk fibre scaffold. XRD, FTIR and SEM-EDAX analysis was performed to characterize the composite. The characterized composite was investigated for its physical properties (porosity and mechanical studies) and biological studies (antimicrobial activity, hemocompatibility, bioactivity). The fabricated composite showed high porosity and the highest tensile strength of 34 MPa, with elongation at a break of 35.82 for the composite. The antimicrobial activity of the composite was studied and the zone of inhibition was measured around 51 ± 0.54 for E. coli, 48 ± 0.48 for S. aureus and 50 ± 0.26 for C. albicans. The hemolytic % was noted around 1.36 for the composite and the bioactivity assay revealed the formation of apatite on composite surfaces.